PERFORMAN SIFAT VEGETATIF, KOMPONEN HASIL, DAN HASIL BERBAGAI VARIETAS KACANG HIJAU (Vigna radiata L.) DI MEDIA GAMBUT - Elfi Rahmadani; Ana Mulyani; Novianti Sunarlim (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2012)
Science Faculty of state Islamic University Sultan Syarif Kasim Riau. The objective of the research was to find the growth and yield of several mungbean varieties in peat media. The experimental design used was randomized complete block design with 15 varieties (Bhakti, Gelatik, Kenari, Kutilang, Betet, Merak, Merpati, Camar, No.129, Nuri, Parkit, Perkutut, Sampeong, Sriti, and Walet), and 3 replications. The variables observed were number days to flower and to harvest, plant height, plant dry weight, number of pods/plant, number of seeds/pod, weight of 100 seeds, and grain yield. Results of the research showed that Gelatik and Kenari varieties flowered faster that the other varieties. Sampeong varieties was the tallest plant at harvest. Different varieties caused different number of pods/plant, weight of 100 seeds and grain yield. However, number of seeds/pod was the same among varieties. Grain yield of No.129 was the lowest among the varieties. From the result of weight of 100 seeds and grain yield its was conducded that seven varieties (Bhakti, Kutilang, Betet, Nuri, Parkit, Perkutut, dan Sampeong) could be planted in peat media.